Кодовое название - "Тихий": военные повести / Петр Петрович Любомиров - Любомиров Петр Петрович (Удмуртия, 1984)
Экземпляры: 2 (20160414) / Инвентарный номер: 7325 / Цена: 0.50 / Сис.шифр: Р2 / Авт.знак: Л93 / ББК: С(Удм)